Difficulty in identifying the Tariff Item: Export of pure vicuña fiber garments - Linares Vizcarra, Mitzi Lourdes Del carmen (2019)
The investigation focused on determining the impact of the difficulty in identifying the content of the tariff item in customs policy and export dynamism of pure vicuña fiber clothing to the US market 2005-2017. Methodology: the population was constituted by tariff items 2005-2017. Results: (a) The difficulty in identifying the content of the tariff item in customs policy negatively affected the export operations of vicuña fiber clothing in category 51 during the 2013-2017 period; (b) The difficulty in identifying the content of the tariff item in customs policy significantly affects the export operations of vicuña fiber clothing to the world during the period from 2005 to 2017. Conclusion: The difficulty of the content of The tariff item in customs policy negatively affects the export dynamism of vicuña fiber clothing to the US market, since it was verified that the export value in thousands of US dollars for the period 2015, 2016 and 2017 are statistically similar (Test H 'Kruskal Wallis 0.063; p 0.969).